2019
DOI: 10.1101/748319
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Integrator complex cleaves nascent mRNAs to attenuate transcription

Abstract: words)Cellular homeostasis requires transcriptional outputs to be coordinated, and many events post transcription initiation can dictate the levels and functions of mature transcripts. To systematically identify regulators of inducible gene expression, we performed high-throughputRNAi screening of the Drosophila Metallothionein A (MtnA) promoter. This revealed that the Integrator complex, which has a well-established role in 3' end processing of small nuclear RNAs (snRNAs), attenuates MtnA transcription during… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
13
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 61 publications
4
13
1
Order By: Relevance
“…Our analysis of protein-coding genes argues that this phenomenon is not just restricted to loci producing cryptic transcripts. Moreover, it suggests that TSS-proximal termination events may extend well beyond previously reported examples (Elrod et al, 2019;Iasillo et al, 2017;Kamieniarz-Gdula et al, 2019;Ogami et al, 2017;Tatomer et al, 2020).…”
Section: Discussionsupporting
confidence: 75%
“…Our analysis of protein-coding genes argues that this phenomenon is not just restricted to loci producing cryptic transcripts. Moreover, it suggests that TSS-proximal termination events may extend well beyond previously reported examples (Elrod et al, 2019;Iasillo et al, 2017;Kamieniarz-Gdula et al, 2019;Ogami et al, 2017;Tatomer et al, 2020).…”
Section: Discussionsupporting
confidence: 75%
“…Possibly the Integrator complex is responsible for these cleavage sites as a way to regulate PTT. Indeed recent studies have shown that Integrator complex prematurely terminates protein coding genes (Elrod et al, 2019; Tatomer et al, 2019) and also terminates transcription of long noncoding RNA genes (Lai et al, 2015). This suggests that the PTT may be regulated by a combination of CPA and Integrator complexes, similar to termination of lncRNA transcription (Nojima et al, 2018b).…”
Section: Discussionmentioning
confidence: 99%
“…Another important role of Integrator is in the promoter-proximal termination of proteincoding gene transcription (Elrod et al, 2019;Lykke-Andersen et al, 2020;Tatomer et al, 2019). Increased full-length transcription of a subset of genes is seen in its absence reflecting escape from this early termination.…”
Section: Comparison Of Zc3h4 and Integrator Effectsmentioning
confidence: 99%